Relevansi Pemikiran Ekonomi Ibnu Khaldun dengan Konsep Ekonomi Pancasila Mubyarto - Ja’far Shodiq; Muhammad Nizar; Muhammad Fahmul Iltiham (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Ibn Khaldun's economic thinking and the concept of Pancasila Economics developed by Mubyarto have significant relevance in understanding an economic system based on moral and social values. Ibn Khaldun emphasized the importance of cooperation, justice, and the role of the state in creating social welfare, which is in line with the basic principles of Pancasila Economics which place the economy as a tool to achieve social justice. This study aims to analyze the harmony between Ibn Khaldun's economic thinking and the concept of Pancasila Economics using a qualitative-descriptive approach through literature studies. The results of the study show that these two thoughts have similarities in aspects of the role of the state in the economy, distribution of justice, and social welfare based on ethical values and togetherness. This study contributes to providing a historical and philosophical perspective on the development of an economic system that is more oriented towards people's welfare and the principles of social justice in Indonesia.